Comparative Study of 30-Meter Running Ability Between Male and Female Elementary School Students - Dian Malini; Dhiki Tamsar Ramadhan; Imam Abdullah; Muh. Rahman Nur Handa; Wibryan Fauzan Takdir (Journal of Physical Education, Sport, and Human Performance, 2025)
Speed is one of the primary components of physical fitness and an important indicator of motor development among elementary school students. Obervations at UPT SPF SD Inpres Karunrung indicate that male students tend to have faster running performance than female students, although empirical evidence remains limited. This study aims to analyze differences in 30-meter sprint ability between male and female students and evaluate whether gender significantly influences sprint performance. The research employed a comparative quantitative approach. The sample was selected using purposive sampling. The instrument used was a 30-meter sprint test conducted twice, with the best time recorded as the final result. Data were analyzed using an independent sample t-test to determine significant differences between groups. The average running time for male students was 4.47 ± 0.41 seconds, while female students recorded 5.14 ± 0.85 seconds. Although there was a descriptive difference, the t-test showed a p-value of 0.151 (>0.05), indicating that the difference was not statistically significant. These findings indicate that gender does not have a significant influence on sprint ability among elementary school students. Speed ability at this age is more determined by motor experience, physical activity level, and movement coordination.